PICTURE SERIES STRATEGY IN PROCEDURE TEXT: ARE STUDENTS EFFECTIVE WORKING IN GROUPS OR INDIVIDUALLY? - Advianti, Vina (Satya Widya, 2025)
This research explored the effectiveness of collaborative group work versus individual work in completing procedural text tasks using a picture series strategy among tenth-grade students of SMK Diponegoro Depok Yogyakarta. The study involved 22 students, each of whom completed two tasks in both group and individual settings. Before assigning the tasks, a questionnaire was distributed to collect data on students' work preferences and their understanding of procedural texts. The four tasks were administered in two separate sessions to avoid fatigue and ensure the quality of the work. Task results were analyzed using descriptive statistical methods, supplemented by qualitative insights from interviews, to assess academic performance and student preferences. The findings indicate that students achieved higher average grades when working in groups (100 in grade 1 and 87.44 in grade 2) compared to individual work (89.48 in grade 1 and 92.14 in grade 2). Additionally, 78.9% of students expressed a preference for group work, citing enhanced understanding through group discussions and mutual support in problem-solving. Interviews highlighted that picture series were effective in helping students visualize and comprehend procedural steps, though some challenges with picture clarity and size were noted.